Investigation and analysis of etiology associated with porcine respiratory disease complex in China from 2017 to 2021 - Sun, Qi; Yu, Xuexiang; He, Dongxian; Ku, Xugang; Hong, Bo; Zeng, Wei; Zhang, Haifeng; He, Qigai (Frontiers in Veterinary Science, 2022)
Porcine respiratory diseases complex (PRDC) is a highly serious threat to the pig industry. In the present study, we investigated and analyzed the etiology associated with PRDC and explored the role of viruses in respiratory bacterial infections. From 2017 to 2021, clinical samples were collected from 1,307 pigs with typical respiratory symptoms in 269 farms in China and screened for pathogens related to PRDC by PCR and bacterial isolation. The results indicated that PRRSV (41.16%, 95%CI: 38.49~43.83%), PCV2 (21.58%,95%CI: 19.35~23.81%), S. suis (63.50%, 95%CI: 60.89~66.11%), and G. parasuis (28.54%, 95%CI: 26.09~30.99%) were the most commonly detected pathogens in pigs with PRDC in China. The dominant epidemic serotypes (serogroups) of S. suis, G. parasuis, and P. multocida were serotype 2, serotype 1, and capsular serogroups D, respectively. Pigs of different ages exhibited different susceptibilities to these pathogens, e.g., PRRSV, PCV2, and G. parasuis had the highest detection rates in nursery pigs, whereas fattening pigs had the highest detection rates of P. multocida and A. pleuropneumoniae. Among the 1,307 pigs, the detection rates of S. suis, G. parasuis, P. multocida, and B. bronchiseptica were higher in virus-positive pigs, especially G. parasuis and P. multocida were significantly (p < 0.01) higher than in virus-negative pigs. In addition, a strong positive correlation was found between coinfection by PRRSV and G. parasuis (OR = 2.33, 95%CI: 1.12~2.14), PRRSV and P. multocida (OR = 1.55, 95%CI: 1.12~2.14), PCV2 and P. multocida (OR = 2.27, 95%CI: 1.33~3.87), PRRSV-PCV2 and S. suis (OR = 1.83, 95%CI: 1.29~2.60), PRRSV-PCV2 and G. parasuis (OR = 3.39, 95%CI: 2.42~4.74), and PRRSV-PCV2 and P. multocida (OR = 2.09, 95%CI: 1.46~3.00). In summary, PRRSV, PCV2, S. suis, and G. parasuis were the major pathogens in pigs with PRDC, and coinfections of two or more PRDC-related pathogens with strong positive correlations were common in China, such as PRRSV and G. parasuis, PRRSV and P. multocida, PCV2 and P. multocida, and also PRRSV-PCV2 and G. parasuis and PRRSV-PCV2 and P. multocida.